Prevalence of Splenic Injury in the Blunt Abdomen Trauma: A Cross- Sectional Study - Rabia Arshad, Aurangzeb Khan, Shaheen Gul Bhatti, Muhammad Mubashir Ahmed Chandio, Seema Nasir, Shah Nawaz Khatti (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Blunt trauma to the abdomen most commonly leads to injury of the spleen. Patients usually presents with left hypochondriac pain or generalized abdominal pain which may radiate to the left shoulder. There can be associated left lower rib fractures. Diagnosis is made on contrast enhanced computed tomography (CT) of the abdomen. Surgical management is warranted in the cases according to AAST Grade of injury. Missed or delayed presentation of injury can lead to mortality hence careful evaluation of mode of injury, complete examination, appropriate investigation and monitoring are vital for patient management. Objective: The present study aims at the determination of incidence and causes of splenic injury after blunt trauma to the abdomen. Study design: A cross-sectional study Place and Duration: This study was conducted at Rawalpindi Medical University from November 2020 to November 2022 Methodology: A total of 195 patients were included in the study. The lowest age limit was 15 years and patients of both genders were considered. The patients with abdominal trauma were received in the emergency department. A detailed history of the event was taken from all the patients with simultaneous resuscitation. After that, a thorough clinical examination was performed on all the patients. The patients were sent for a FAST SCAN and CCET abdomen to diagnose and assess the extent of the injury. The type of trauma that lead to the injury of the spleen, such as road traffic accident (RTA), assault, and fall from height was recorded of each patient. Patients with AAST grade I and II were managed conservatively except in cases where exploration was required for concomitant abdominal injuries however patients with Grade III, IV and V underwent exploration, spleenoraphy or splenectomy respectivelyThe data was collected and analyzed in the IBM SPSS version 26. Result: A total of 195 patients were studied, out of which 48 (24.61%) were female and 147 (75.38%) were male. The mean age of the patients was 30.45±2.12 years. Overall 12 (6.15%) were detected with splenic injury. A total of 5 (41.67%) had an RTA, 4 (33.33%) had a fall from height, 2 (16.67%) assault, and 1 (8.33%) had sports injury. Conclusion: The most common type of blunt trauma to the abdomen which resulted in a splenic injury was road traffic accidents followed by fall from height. Early diagnosis is helpful in the proper management of the patient and increasing the survival rate. Keywords: Splenic injury, road traffic accident, blunt trauma